Strategi Pembelajaran Al-Qur’an untuk Anak Usia Dini pada Program Magrib Mengaji - Hasibuan, Fatimah; Primanisa, Reiska (AUD Cendekia: Journal of Islamic Early Childhood Education, 2025)
This study aims to describe the Qur’an learning strategies for early childhood in the Magrib Mengaji program at Masjid Muslimin and to analyze the supporting factors, obstacles, and children’s responses to its implementation. The study employed a qualitative method with a case study approach at Masjid Muslimin, which routinely holds the program daily after Maghrib prayer. Data were collected through in-depth interviews with five Qur’an teachers, two mosque administrators, eight parents, as well as participatory observation and documentation involving six early childhood students as supporting informants. Data analysis was conducted using Miles and Huberman’s interactive model, including data reduction, presentation, and conclusion drawing, complemented by source, technique, and time triangulation. The findings show that the Qur’an learning strategies combine traditional methods (talaqqi, Iqra’) and innovative methods (games, songs, Islamic stories), tailored to the characteristics of early childhood. The learning process includes preparation, implementation, and informal evaluation, emphasizing teacher role modeling, habituation of manners, positive motivation, and social interaction. Supporting factors include teacher dedication, children’s enthusiasm, parental support, and a conducive mosque environment, while obstacles include limited media, inconsistent attendance, limited parental involvement, and short learning time.